Self-Sovereignty for Refugees? The Contested Horizons of Digital Identity. Issue 1 (1st January 2022) - Cheesman, Margie
ABSTRACT: This paper critically examines the implications of 'self-sovereign identity' (SSI) for border politics and migration management. SSI refers to user-controlled, decentralised forms of digital identification. Closely linked with the distributed ledger technology blockchain, SSI is presented by advocates as a tool to empower marginalised groups, including refugees. Among other benefits, some claim that SSI removes the need for powerful, centralised institutional structures by giving individuals control and ownership of their identity information. However, through ethnographic research in an international aid organisation, I find that SSI is an embryonic technology with indeterminate properties and benefits. I identify a series of competing logics in the debates around SSI's emancipatory potential, which relate to four issues: (i) the neutrality of the technology, (ii) the capacities of refugees, (iii) global governance and the nation state, and (iv) new economic models for digital identity. SSI is simultaneously the potential enabler of new modes of empowerment, autonomy and data security for refugees and a means of maintaining and extending bureaucratic and commercial power. I situate SSI in a genealogy of systems of identity control and argue that, in practice, it is likely to feed into the powers of corporations and states over refugee populations.